Influence of land use change on rove beetle diversity: A systematic review and global meta-analysis of a mega-diverse insect group. (March 2021) - Méndez-Rojas, Diana M.; Cultid-Medina, Carlos; Escobar, Federico
Graphical abstract: Highlights: Global response of rove beetle communities to land use change is evaluated. Species density and interpolated richness decrease with increasing land use change. Crops and pastures drive species density loss; the extent depends on the region. Local rove beetle response is clear but the role of landscape context is unknown. Reasons for using rove beetles as ecological disturbance indicators are highlighted. Abstract: The global decline in insect diversity is worrisome and little is known about insects' response to land use change. Rove beetles (Staphylinidae) are megadiverse and a key component in ecosystem functioning as generalist predators in forest habitats and agroecosystems. These beetles are sensitive to environmental changes related to the modification of natural habitats, however there is still no consensus on their usefulness as potential ecological disturbance indicators. Through an exhaustive literature review and a global quantitative analysis, we evaluated the response of rove beetles to land use change in different biogeographic regions to see if these beetles can be used as an ecological disturbance indicator. Using Hill's series ( q D), species density and the density of individuals, rove beetle response was evaluated for different types of land use ranging from native habitats to crops and urban zones . Rove beetle density and richness respond negatively to crops and pastures, but urban zones were as diverse as some native habitats. The magnitude of the response varied among biogeographic regions and appears to be related to the life history traits of the species that make up the beetle communities. The high degree of variation observed in the response of rove beetles might result from the lack of information about the influence of the landscape's characteristics on local response. The idea that the simplification of native habitats leads to a reduction in rove beetle density and diversity is partially supported. However, in order to generalize a pattern of rove beetle response to the global scale, it is necessary to standardize the protocol for comparative studies in addition to considering other community attributes (e.g. species composition). The use of Staphylinidae as a potential ecological disturbance indicator in human-dominated landscapes is widely discussed.